Arsenic pollution and arsenic-resistant bacteria of drying Urmia Salt Lake - Haghi, Morteza; Diznabi, Salar H.; Karaboz, Ismail; Ersoy Omeroglu, Esra (Frontiers in Environmental Science, 2023)
Extensive arsenic contamination of groundwater, rivers, and agricultural farms has led to widespread arsenic poisoning and consequent problems associated with health and economy. In recent years, many studies have been performed to understand bacterial arsenic detoxification and metabolism which has paved the way for bioremediation applications. This study attempted to isolate and characterize arsenic-resistant bacteria from the drying Urmia lake. As a result of the 16S rDNA analysis, six arsenic-resistant strains were identified as the members of Shouchella, Salipaludibacillus, and Evansella genera. For some of the strains, the maximum tolerance concentration for either arsenate or arsenite was considerably high, 320 and 16 mM, respectively. All the strains harbored the arsenate reductase gene (arsC). The arsenate permease (arsB) gene was identified in all strains except in strains S1, S12, and E15. The metabolic genes of respiratory arsenate reductase (arrB) and arsenite oxidase (arxA) were identified in none of these strains. This feature of the strains with the arsC gene region can be exploited to bioremediate arsenic from contaminated areas by using a two-step process. The second step can be carried out by the adsorption of arsenite to iron oxide or by precipitation with sulfide. Today, more and more ecosystems are being destroyed due to anthropogenic pollution, and it is important to reveal the negative effects and solutions of this situation on the ecosystems. So, the current study provides a potential source of bacteria for such studies that implement bioremediation practices to prevent arsenic catastrophe in vicinal territories, and reveals arsenic pollution in Urmia lake.